Mining predicate rules without minimum support threshold - Ahmad, Hafiz Ishfaq; Sim, Alex Tze Hiang; Roliana Ibrahim; Shah, Syed Mazhar Ali; Abrar, Mohammad; Gul, Asma (Kuwait Journal of Science, 2021)
Association rule mining (ARM) is used for discovering frequent itemsets for interesting relationships of associative and correlative behaviors within the data. This gives new insights of great value, both commercial and academic. The traditional ARM techniques discover interesting association rules based on a predefined minimum support threshold. However, there is no known standard of an exact definition of minimum support and providing an inappropriate minimum support value may result in missing important rules. In addition, most of the rules discovered by these traditional ARM techniques refer to already known knowledge. To address these limitations of the minimum support threshold in ARM techniques, this study proposes an algorithm to mine interesting association rules supportlessly using predicate logic and a property of a proposed interestingness measure ( measure). The algorithm scans the database and uses measure’s property to search for interesting combinations. The selected combinations are mapped to pseudo-implications and inference rules of logic are used on the pseudo-implications to produce and validate the predicate rules. Experimental results of the proposed technique show better performance against state-of-the-art classification techniques, and reliable predicate rules are discovered based on the reliability differences of the presence and absence of the rule’s consequence.